Loss and gain of sexual reproduction in the same stick insect - Mary Morgan‐Richards; Shelley S. Langton‐Myers; Steven A. Trewick (Molecular Ecology, 2019)
The outcome of competition between different reproductive strategies within a single species can be used to infer selective advantage of the winning strategy. Where multiple populations have independently lost or gained sexual reproduction it is possible to investigate whether the advantage is contingent on local conditions. In the New Zealand stick insect Clitarchus hookeri , three populations are distinguished by recent change in reproductive strategy and we determine their likely origins. One parthenogenetic population has established in the United Kingdom and we provide evidence that sexual reproduction has been lost in this population. We identify the sexual population from which the parthenogenetic population was derived, but show that the UK females have a post‐mating barrier to fertilisation. We also demonstrate that two sexual populations have recently arisen in New Zealand within the natural range of the mtDNA lineage that otherwise characterizes parthenogenesis in this species. We infer independent origins of males at these two locations using microsatellite genotypes. In one population, a mixture of local and nonlocal alleles suggested males were the result of invasion. Males in another population were most probably the result of loss of an X chromosome that produced a male phenotype in situ. Two successful switches in reproductive strategy suggest local competitive advantage for outcrossing over parthenogenetic reproduction. Clitarchus hookeri provides remarkable evidence of repeated and rapid changes in reproductive strategy, with competitive outcomes dependent on local conditions.

Spatial genetics of a high elevation lineage of Rhytididae land snails in New Zealand: the Powelliphanta Kawatiri complex - Elizabeth E. Daly; Kathleen J. Walker; Mary Morgan-Richards; Steven A. Trewick (Molluscan Research, 2019)